2007
DOI: 10.1111/j.1440-1843.2007.01104.x
|View full text |Cite
|
Sign up to set email alerts
|

Directly measured cabin pressure conditions during Boeing 747–400 commercial aircraft flights

Abstract: Cabin pressure is determined only by the engineering of the aircraft and its altitude and in the present study was always higher than required by regulation. Current fitness-to-fly evaluations simulate cabin conditions that passengers will not experience on these aircraft. There may be increased risks to patients should new or older aircraft operate nearer to the present minimum standard.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
23
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 12 publications
(16 reference statements)
0
23
0
1
Order By: Relevance
“…Planes authorized above 25,000 ft must be equipped with systems such that cabin occupants are not exposed to cabin altitudes greater than 25,000 ft in the event of cabin pressure system failure ( 10 ). In a study of actual cabin pressures on commercial fl ights, one set of researchers found average relative altitudes to vary yet remain well within guidelines, averaging a maximum relative altitude of 6500 ft above sea level ( 8 ). Although cabin pressure is maintained at a relative altitude much lower than that actually experienced by the aircraft, computer modeling research has shown that the effect of air travel on a patient with intracranial air can signifi cantly raise intracranial pressure (ICP; 2 ).…”
Section: Discussionmentioning
confidence: 98%
“…Planes authorized above 25,000 ft must be equipped with systems such that cabin occupants are not exposed to cabin altitudes greater than 25,000 ft in the event of cabin pressure system failure ( 10 ). In a study of actual cabin pressures on commercial fl ights, one set of researchers found average relative altitudes to vary yet remain well within guidelines, averaging a maximum relative altitude of 6500 ft above sea level ( 8 ). Although cabin pressure is maintained at a relative altitude much lower than that actually experienced by the aircraft, computer modeling research has shown that the effect of air travel on a patient with intracranial air can signifi cantly raise intracranial pressure (ICP; 2 ).…”
Section: Discussionmentioning
confidence: 98%
“…Commercial air travel may be preferred, even for patient transport with health care personnel. One must recognize that cabin air pressure in commercial long haul aircraft is normally between 6000 and 8000 ft. depending on the airframe type and age, though cabin pressures in commercial passenger airframes have been reported to be as ‘high’ as 9000 ft [18, 19]. It is prudent to confirm the absence of intracranial air in any post-craniotomy (recent) patient scheduled for air transport on a commercial aircraft, rather than risk an unplanned diversion of a jumbo-jet due to symptoms developing during ascent related to reasonably anticipated IC air expansion.…”
Section: Discussionmentioning
confidence: 99%
“…One study revealed that average cabin altitude across 207 commercial flights was 6341 ft with longer flights resulting in higher average altitudes [6]. Another study revealed an average pressure of 634 mmHg across 45 commercial flights and three airlines in Boeing 747 airplanes [7]. This represents a decrease in the partial pressure of oxygen of greater than 15% from that of sea level.…”
Section: Discussionmentioning
confidence: 99%